Perampanel in brain tumor‐related epilepsy: Observational pilot study - Maschio, Marta (Brain Behav, 2020)
OBJECTIVE: Possible loss of efficacy and potential interactions between antiepileptic drugs (AEDs) and chemotherapy could complicate the management of patients with brain tumor‐related epilepsy (BTRE) that may expose patients to an increased risk of adverse events. Perampanel (PER) is a highly selective, noncompetitive, alpha‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazole propionic acid (AMPA)‐type glutamate receptor antagonist. This study evaluates the effectiveness, QoL, cognition, and mood of PER in add‐on therapy in BTRE patients. MATERIAL AND METHODS: Observational pilot study on the effectiveness of PER as add‐on therapy in BTRE patients with uncontrolled seizures with a 6‐month follow‐up. RESULTS: We recruited 26 BTRE patients. During the follow‐up, 16 underwent chemotherapy and 11 radiotherapy; 11 had disease progression. Five patients dropped out. Mean daily PER dosage was 6.6 mg in the 21 patients who completed the follow‐up and 6.4 mg in the ITT population. The mean number of seizures/month decreased from 10.8 ± 15.03 at baseline to 1.7 ± 4.34 in the 21 patients who reached the final follow‐up. Responder rate was 88.4%: Eight patients were seizure‐free, 15 had ≥50% seizure reduction, and 3 remained stable. Four patients (15.4%) reported AEs: 2 required PER dose reduction, and 2 dropped out. Neuropsychological, mood, and QoL questionnaires were not statistically different compared to baseline. There were no significant differences in seizure control in patients with/without IDH1 mutation and with/without MGMT methylation. CONCLUSIONS: Perampanel proved to be effective on seizure control in BRTE patients and to be well tolerated without negative effects on cognition and QoL. Perampanel could be a valid therapeutic option in BTRE.